The why and how of working with communities through collective impact. Issue 2 (14th March 2016) - Raderstrong, Jeff; Boyea-Robinson, Tynesia
Abstract: How to better involve community members in collective impact initiatives has been a central question for many collective impact practitioners. This article presents a synthesis of research surrounding the questions of why community members must be more involved in collective impact, and how to better involve them. The synthesis was developed through a literature review, semi-structured interviews, and an online course on the topic marketed toward practitioners. After discussing the need to align community engagement strategies with the goals of a collective impact initiative, the discussion presents two dimensions of community engagement strategies: amplifying the voice of community members within a collective impact initiative, and incorporating that voice into the collective impact initiative using feedback loops. Finally, several strategies are presented showing how collective impact practitioners can grow their capacity in these areas.